2019
DOI: 10.3390/nu11092235
|View full text |Cite
|
Sign up to set email alerts
|

Potential Oral Health Care Agent from Coffee against Virulence Factor of Periodontitis

Abstract: Background: Coffee is a major dietary source of polyphenols. Previous research found that coffee had a protective effect on periodontal disease. In this study, we aimed to investigate whether coffee extract and its primary phenolic acid, chlorogenic acid, affect the growth and protease activity of a periodontopathogen Porphyromonas gingivalis (P. gingivalis). Methods: Coffee extract and chlorogenic acid were prepared by a two-fold serial dilution. The turbid metric test and plate count method were used to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 55 publications
(61 reference statements)
0
32
0
Order By: Relevance
“…Gov et al demonstrated in an in vitro study that coffee components significantly reduced VSC levels and VSC-producing bacteria [ 17 ]. It has been reported in several studies that coffee extracts contain substances that have both antimicrobial and antioxidant activities [ 16 , 31 , 32 , 33 ]. Roasted coffee’s antibacterial activity was attributable to the presence of compounds like caffeine, α-dicarbonyl, glyoxal, methylglyoxal, and diacetyl [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gov et al demonstrated in an in vitro study that coffee components significantly reduced VSC levels and VSC-producing bacteria [ 17 ]. It has been reported in several studies that coffee extracts contain substances that have both antimicrobial and antioxidant activities [ 16 , 31 , 32 , 33 ]. Roasted coffee’s antibacterial activity was attributable to the presence of compounds like caffeine, α-dicarbonyl, glyoxal, methylglyoxal, and diacetyl [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Roasted coffee’s antibacterial activity was attributable to the presence of compounds like caffeine, α-dicarbonyl, glyoxal, methylglyoxal, and diacetyl [ 34 ]. More specifically, in vitro studies have demonstrated that coffee extract has antibacterial effects against P. gingivalis , and Prevotella intermedia , which are the bacteria closely associated with halitosis [ 16 , 35 , 36 ]. Furthermore, the coffee extract can inhibit protease production by P. gingivalis [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study reported that coffee consumption might be an independent risk indicator of periodontal disease in Korean adults [ 14 ]. One study also showed that chlorogenic acid in coffee has antimicrobial activity and reduces the protease activity of Porphyromonas gingivalis [ 16 ]. Porphyromonas gingivalis is one of the bacteria implicated in bacterial plaque biofilms, and it contributes to the progression of periodontal disease [ 17 ].…”
Section: Introductionmentioning
confidence: 99%